A Property of Azarin’s Limit Set of Subharmonic Functions - Chouigui, A.; Grishin, A. F. (Журнал математичної фізики, аналізу, геометрії, 2008)
Let v(z) be a subharmonic function of order ρ>0, and Fr(v) be the limit set in the sense of Azarin. Let z be fixed and I(z)={u(z):uFr(v)}. We prove that I(z) is either a closed interval or a semiclosed interval which does not contain its infimum. Mathematics Subject Classification: 31A05.